Phylogenetical Position versus Pollination Syndromes: Floral Trichomes of Central American and Mexican Pinguicula - Lustofin, Krzysztof; Świątek, Piotr; Miranda, Vitor F. O. [UNESP]; Płachno, Bartosz J. (MDPI, 2023)
Central American and Mexican Pinguicula species are characterized by enormous divergence in size and color of flowers and are pollinated by butterflies, flies, bees, and hummingbirds. It is known that floral trichomes are key characters in plant–pollinator interaction. The main aim of our study was to verify our hypothesis that the distribution and diversity of non-glandular and glandular trichomes are related to the pollinator syndromes rather than the phylogenetic relationships. The studied sample consisted of Central American and Mexican species. In our study, we relied on light microscopy and scanning electron microscopy with a phylogenetic perspective based on ITS DNA sequences. The flower morphology of species pollinated by butterflies and hummingbirds was similar in contrast to species pollinated by flies and bees. Species pollinated by butterflies and hummingbirds contained low diversity of non-glandular trichomes, which occurred mostly in the tube and basal part of the spur. Surprisingly, in P. esseriana and P. mesophytica, non-glandular trichomes also occurred at the base of lower lip petals. In the case of species pollinated by flies/bees, we observed a high variety of non-glandular trichomes, which occurred on the surface of corolla petals, in the tube, and at the entrance to the spur. Furthermore, we did not identify any non-glandular trichomes in the spur. The capitate glandular trichomes were of similar morphology in all examined species. There were minor differences in the shape of the trichome head, as well as the length and the number of stalk cells. The distribution and the diversity of non-glandular and glandular trichomes and pollinator syndromes were mapped onto a phylogenetic reconstruction of the genus. Most micromorphological characters appear to be associated more with floral adaptation to pollinators and less with phylogeny.
Keywords: carnivorous plants; flower micromorphology; phylogeny; Pinguicula; trichomes